NK Cells Regulate CD8+ T Cell Mediated Autoimmunity - Lang, Philipp A.; Crome, Sarah Q.; Xu, Haifeng C.; Lang, Karl S.; Chapatte, Laurence; Deenick, Elissa K.; Grusdat, Melanie; Pandyra, Aleksandra A.; Pozdeev, Vitaly I.; Wang, Ruifeng; Holderried, Tobias A. W.; Cantor, Harvey; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Elucidating key factors that regulate immune-mediated pathology in vivo is critical for developing improved strategies to treat autoimmune disease and cancer. NK cells can exhibit regulatory functions against CD8+ T cells following viral infection. Here we show that while low doses of lymphocytic choriomeningitis virus (LCMV-WE) can readily induce strong CD8+ T cell responses and diabetes in mice expressing the LCMV glycoprotein on -islet cells (RIP-GP mice), hyperglycemia does not occur after infection with higher doses of LCMV. High-dose LCMV infection induced an impaired CD8+ T cell response, which coincided with increased NK cell activity during early time points following infection. Notably, we observed increased NKp46 expression on NK cell during infection with higher doses, which resulted in an NK cell dependent suppression of T cells. Accordingly, depletion with antibodies specific for NK1.1 as well as NKp46 deficiency (Ncr1gfp/gfp mice) could restore CD8+ T cell immunity and permitted the induction of diabetes even following infection of RIP-GP mice with high-dose LCMV. Therefore, we identify conditions where NK cells can play a regulatory role and interfere with CD8 T cell mediated tissue specific pathology.